Investigating Crescentic Glomerulonephritis in Children: Clinical Spectrum and Predictors of Renal Survival: Crescentic Glomerulonephritis - Gupta, Nikita; Ohri, Alpana; Udani, Amish; Shah, Chintan (Journal of Pediatric Nephrology, 2023)
Background and Aim: This study aims to evaluate the clinical and histopathological profile in children with crescentic glomerulonephritis (CGN) and determine the predictors of renal outcome. Methods: In this retrospective study, we reviewed all native kidney biopsies performed in patients <18 years over 9 years (2011-2019). Individuals with ≥20% crescents with follow-up for at least 1 year were enrolled. Results: This study included 34 patients. The most common variety was immune-complex glomerulonephritis (GN) (type II CGN) (n=21; 62%), including patients with Henoch- Schonlein purpura (n=6), lupus nephritis (n=6), post-infectious GN (n=3), C3GN (n=3), and dense deposit disease (n=3). The second most common was pauci-immune GN (type III CGN; n=12; 35%) followed by anti-glomerular basement membrane disease (type I CGN; n=1; 3%). Hypertension (88%), hematuria (84.2%), and oliguria (64%) were the most common presenting features. The outcome predictors for poor renal survival were the presence of oliguria (HR-5.11, P=0.035), severe hypertension (HR-11.51, P=0.019), estimated glomerular filtration rate <15 mL/min/1.73 m2 at presentation (HR-5.05, P=0.007), percentage of crescents (HR-10.66, P=0.001), presence of fibrous crescents (HR-6.34, P=0.001), and interstitial fibrosis and tubular atrophy (HR-8.88, P=0.0046). The overall outcome of the study revealed complete recovery (n=12), partial recovery (n=6), chronic kidney disease (n=3), and end-stage renal disease (n=13). The renal survival in patients with ≥50% crescents was poor (P=0.037) as compared to subjects with <50% crescents. Conclusion: Renal survival can be predicted by the severity of presenting features and histopathological markers. Two-thirds of patients had type II CGN with renal survival outcomes similar to type III CGN. The percentage of crescents is the most important predictor of renal survival.